41.9k views
4 votes
7 (r3+15r² +48r – 44) = (r+6)​

User CurtLH
by
5.2k points

2 Answers

3 votes

Answer:


(-178 + and - √(64654) )/(105)

Explanation:

Advanced equations like these fit perfect to do the quadratic formula

first we must find a,b and c

A=
x^(2)

B=constant multiplied by x

C=constant not multiplied by x

Alright now that we established that we need to format the equation to equal 0 so it will basically look like this
a^(2)+b+c=0

First add like terms

7 (51r +
15^(2) -44) = r + 6

Then we do the distributive property

357r +
105r^(2) -308 = r + 6

Then we inverse the R + 6 so we can make the equation equal 0

so 357r +
105r^(2) -308-r-6 = 0

Add like terms again

356r +
105r^(2) -314=0

Now we have our A B and C!!! So lets put it in the quadratic formula

I like to find the discriminant first which is
b^(2) -4ac so lets plug everything in.

356
356^(2) -4(105)(-314)

and that equals

258616 but that isn't a perfect square so we'll need to factor it so lets keep it fragmented for the time being


\frac{-316+ and -\sqrt{356^(2)+131880 } }{210}

is our current expression

The easiest thing to factor out is
2^(2)

So that should equal


\frac{-356+ and -\sqrt{2^(2) *64654} }{210}

Square
2^(2)


(-356+and-2√(64654) )/(210)

now the only thing left to do is divided every thing by the greatest common factor which is 2, we don't divided whatever is in the
√(x) when doing this step

so the final solution is


(-178+ and -√(64654) )/(105)

User Remmy
by
5.2k points
4 votes

Answer:

r=−9.403283,−6.348173,0.751456

Explanation:

Let's solve your equation step-by-step.

7(r3+15r2+48r−44)=r+6

7r3+105r2+336r−308=r+6

Step 1: Subtract r+6 from both sides.

7r3+105r2+336r−308−(r+6)=r+6−(r+6)

7r3+105r2+335r−314=0

Step 2: Use cubic formula.

r=−9.403283,−6.348173,0.751456

User NoviceToDotNet
by
4.9k points